Synthesis and Characterization of Pyridino(1,4-Η-cyclohexa-1,3-diene)Derivatives of Iron Tricarbonyl Complexes - T. I. Odiaka; O. F. Akinyele; I. A. Adejoro (E-Journal of Chemistry)
In this synthesis, we have been able to show that, the addition of x- substituted pyridines, (X = H, 2- Me, 3- Me 4- Me, 4-NH2 and 4-N(CH3)2 to the dienyl ring of the organometallic cation, [(Fe(CO)3 (1-5- η-2-Me0C3H6)]BF4 and [(Fe(CO)3(1-5-η-C6H7)]BF4 gives ionic substituted diene products, (X C5H4-C6H6Y (Fe(CO)3] BF4,Y=H or 2-MeO. The reaction takes place at ordinary room temperature. The resulting products were isolated and characterized.